Age-Related Changes in Thymic Central Tolerance - Srinivasan, Jayashree; Lancaster, Jessica N.; Singarapu, Nandini; Hale, Laura P.; Ehrlich, Lauren I. R.; Richie, Ellen R. (Frontiers in Immunology, 2021)
Thymic epithelial cells (TECs) and hematopoietic antigen presenting cells (HAPCs) in the thymus microenvironment provide essential signals to self-reactive thymocytes that induce either negative selection or generation of regulatory T cells (Treg), both of which are required to establish and maintain central tolerance throughout life. HAPCs and TECs are comprised of multiple subsets that play distinct and overlapping roles in central tolerance. Changes that occur in the composition and function of TEC and HAPC subsets across the lifespan have potential consequences for central tolerance. In keeping with this possibility, there are age-associated changes in the cellular composition and function T cells and Treg. This review summarizes changes in T cell and Treg function during the perinatal to adult transition and in the course of normal aging, and relates these changes to age-associated alterations in thymic HAPC and TEC subsets.